A meta-analysis of supplemental enzyme studies in growing-finishing pigs fed diets containing dried distillers grains with solubles: effects on growth performance - J Y Jacela; Joel M DeRouchey; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2009)
A meta-analysis of 4 experiments involving 4,506 pigs was conducted to determine the effects of several commercial enzymes on the growth performance of growing-finishing pigs fed various amounts of dried distillers grains with solubles (DDGS). Experiments 1 and 2 used corn-soybean meal-based diets with 15% DDGS. A Î²-mannanase enzyme (Hemicell; ChemGen Corp., Gaithersburg, MD) was used in enzyme treatments in Exp. 1, and a blend of enzymes that had Î²-glucanase, cellulase, and protease activities (Agri-king REAP; Agri-King, Inc., Fulton, IL) was used in Exp. 2. In Exp. 3, diets containing 45% and 60% DDGS were fed with or without 2 commercial enzyme products designed for use in diets containing DDGS. In Exp. 4, an enzyme product with bacterial endo-1,4-Î²-xylanase was evaluated in diets containing 30% DDGS. All enzyme treatments in each experiment were pooled in a meta-analysis to compare the responses to diets with or without enzyme addition regardless of the other factors tested in each trial. All experiments were conducted in the same commercial swine research facility. There were no differences in ADG (P>0.52), ADFI (P>0.33), F/G (P>0.35), and final weight (P>0.60) among pigs fed diets with added enzyme and pigs fed diets without enzyme in any of the 4 experiments or in the pooled data. In conclusion, on the basis of the combined results from the 4 experiments evaluated in this meta-analysis, adding these enzymes in diets containing various amounts of DDGS does not appear to be beneficial in pigs.; Swine Day, Manhattan, KS, November 19, 2009
Keywords: Swine day; 2009; Kansas Agricultural Experiment Station contribution; no. 10-014-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1020; Dried distillers grains with solubles; Enzyme; Swine